Effects of Substrate Temperature on Vacuum Deposited Thin Film of Disperse Red 1 on ITO Glass - H. Taunaumang; Herman Herman; M. O. Tjia (Institute for Research and Community Services (LPPM) ITB, 2001)
Abstract. Highly crystalline thin films of photorefractive Disperse Red 1 (DR 1) molecule have been fabricated on clean substrate of ITO (indium tin oxide) glass by means of physical vapor deposition at various substrate temperatures. In addition to molecular orientation and organization revealed by their XRD and FTIR spectral characteristic and the enhancement of those effects by substrate temperature, further analysis of FTIR spectrum around nitrobenzene absorption band indicates the formation of strong hydrogen bond resulting in a head-tail stacking of the molecules. The deposited films also show systematic reduction of light absorption in the visible region with increasing substrate temperature. This modification of the optical property is clearly favorable for long wavelength photonic applications of DR1 film. Pengaruh Suhu Substrat pada Film Tipis 'Disperse Red 1' yang Dideposisi pada Gelas ITO dalam VakumSari. Dalam eksperimen ini telah berhasil diperoleh melalui proses deposisi vakum sejumlah film tipis bahan fotorefraktif dari molekul